Obesity-associated metabolic changes influence resting and peak heart rate in women and men. (2nd November 2015) - Strandheim, Astrid; Halland, Hilde; Saeed, Sahrai; Cramariuc, Dana; Hetland, Trude; Lønnebakken, Mai Tone; Gerdts, Eva
Abstract>: Objectives: To study the relationship between obesity and heart rate (HR) in women and men. Design: We studied 241 overweight and obese subjects without known heart disease. All subjects underwent ergospirometry during maximal exercise testing on treadmill and recording of body composition, electrocardiogram and clinic and ambulatory blood pressure. Results: Women ( n = 132) were slightly older and had higher fat mass, but lower weight, blood pressure and prevalence of metabolic syndrome (MetS) than men ( n = 109) (all p < 0.05), while prevalences of obesity and hypertension did not differ. A significant interaction between sex and HR was demonstrated ( p < 0.05). In multivariate analysis, female sex (β = 0.99, p < 0.01) predicted higher resting HR independent of confounders. Higher resting HR was particularly associated with presence of MetS, hypertension, higher insulin resistance and lower relative muscle mass in men (all p < 0.05). Female sex also predicted higher peak exercise HR (β = 0.48, p < 0.01) independent of confounders. Higher peak exercise HR was particularly associated with higher exercise capacity and lower age and self-reported physical activity in men, while lower HbA1c and absence of obesity were the main covariates in women in multivariate analyses (all p < 0.05). Conclusions: In our study population, obesity and obesity-associated metabolic changes influenced both resting and peak exercise HR.